The Effect of Corporate Governance and Environmental, Social, and Governance Performance on Firm Value: Case Study of Energy Sector Companies in Indonesia - Miranda Yuli Zalianty; Azmi, Yanis Ulul (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2025)
Corporate Governance plays a vital role in supporting the increase in Firm Value. When evaluating a company's long-term viability and moral conduct, stakeholders, regulators, and investors are increasingly focusing on environmental, social, and governance (ESG) considerations. Specifically, this study looks into the impact of Corporate Governance and ESG Performance attributes on Firm Value. The theories used are Stakeholder Theory and Institutional Theory. This study considers three Corporate Governance mechanisms, namely diversity attributes, structural attributes, and process attributes that are rarely considered in previous studies. ESG Performance in this study is developed as an innovative index, which differs from previous studies that rely on well-known ESG measurement methods such as Thompson Reuters, MSCI, and other ESG ranking techniques. In addition, this study also uses Profitability, Ownership Concentration, Leverage, and Firm Age as control variables. The data collected is based on the financial report and annual report listed on the Indonesia Stock Exchange (IDX), which is engaged in the energy sector and meets the assessment standards, so a sample of 142 companies is obtained. The testing of the theoretical model was carried out with the assistance of the Statistical Package for the Social Science (SPSS) version 23, and multiple linear regression analysis was utilized in the testing of the model. This finding supports the idea that corporate governance and ESG performance simultaneously affect firm value